The Exploring Students' Perception on the Use of TikTok to Improve Their English Speaking Skill - Nofry Frans; Michelle E, P Mumek; Vera Wahani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study explores students’ perceptions of using TikTok to improve their English-speaking skills. Drawing on survey data from 99 participants, the findings reveal that a majority view TikTok as a helpful and engaging platform for language learning. Over 77% of students agreed or strongly agreed that TikTok supports their speaking development, particularly in areas such as vocabulary acquisition, pronunciation, grammar, and intonation. The platform’s interactive features, including short video challenges and expressive content, were found to boost motivation and reduce anxiety about making mistakes. Students also appreciated the freedom to express themselves and the fun, informal learning environment TikTok provides. These results suggest that integrating social media tools like TikTok into language education can enhance learner confidence and participation. Overall, the study highlights the potential of digital platforms to complement traditional methods and foster meaningful language practice in a way that feels natural and enjoyable to students.